Enhancing the ferroelectric performance of P(VDF-co-TrFE) through modulation of crystallinity and polymorphism. (1st August 2018) - Spampinato, Nicoletta; Maiz, Jon; Portale, Giuseppe; Maglione, Mario; Hadziioannou, Georges; Pavlopoulou, Eleni
Abstract: The functional properties of P(VDF- co -TrFE) are strongly dependent on its structure, which, in turn, depends on processing conditions applied. In this work we investigate the P(VDF- co -TrFE) processing-structure-function relationships, in order to find the thermal conditions that result in optimum ferroelectric performance in thin film configuration. Our results show that annealing temperature affects mostly the remnant polarization value, Pr, while annealing time has a severe effect on the coercive field, Ec . An optimized ferroelectric functionality, in terms of high Pr of about 90 mC/m 2 and low Ec of 50 MV/m, is achieved and rationalized through structural analysis by means of GIWAXS. The best performing structure exhibits a high degree of crystallinity, a preferential orientation of the crystallites with the polymer chains parallel to the substrate and the occurrence of three ferroelectric phases. A deconvolution study demonstrates the presence of a moderately unstable ferroelectric phase that is designated to facilitate ferroelectric switching. Our findings show that a single step of 15 min annealing at 135 °C leads to high performance P(VDF- co -TrFE) structure, proving that the 2 h-long annealing step that is traditionally applied is not necessary. Graphical abstract: Image 1 Highlights: Integrated processing-structure-function study of P(VDF- co -TrFE) films. Annealing temperature affects remnant polarization, time affects the coercive field. Optimized ferroelectric performance is achieved for annealing at 135 °C of 15 min. Three ferroelectric phases are observed in the most performing films. The presence of a moderately unstable ferroelectric phase facilitates switching.